Relationship between the clinical efficacy of probiotics and the intestinal microbiota in patients on maintenance dialysis: a prospective, randomized, double-blind, placebo-controlled study - Tetsuya Ogawa; Yukishige Isomatsu; Kiyotsugu Omae; Nobuo Nagano (Renal Replacement Therapy)
Abstract Background and hypotheses Chronic kidney disease induces systemic inflammation, and probiotics attenuate inflammation. In this study, we report on the serum phosphorus-lowering effect of Bifidobacterium longum and investigate the relationship between the efficacy of probiotics and changes in the intestinal microbiota in patients on maintenance dialysis. Methods The probiotics used were oral formulations that included three active probiotics (Bacillus subtilis, Enterococcus faecium, and Clostridium butyricum). Patients on maintenance dialysis were randomly assigned to a probiotics group (n = 37) or a placebo group (n = 36), and the study drug was administered for 6 months in a double-blind manner. We investigated the involvement of the intestinal microbiota in changes in the high-sensitivity C-reactive protein/albumin ratio (hs-CRP/Alb ratio) and biochemical test values. Changes in the intestinal microbiota were examined by analyzing feces via 16S rRNA gene amplicon sequencing. Results No change was observed in the hs-CRP/Alb ratio in either group. The serum phosphorus level, however, decreased significantly only in the probiotics group. The reduction in serum phosphorus levels was remarkable in patients receiving laxatives. In the probiotics group, the metagenomic data revealed an increase in the abundance of the butyric acid bacteria Lachnoclostridium. Furthermore, the change in butyric acid bacteria was positively correlated, but the change in lactic acid bacteria was negatively correlated with the reduction in the serum phosphorus level. Conclusions For patients on maintenance dialysis, probiotics do not reduce systemic inflammation; however, they lower serum phosphorus levels by regulating the intestinal microbiota balance, especially when probiotics are used in combination with laxatives. The probiotic preparation used may further decrease serum phosphoruslevels.